(untitled) (The Pakistan Development Review, 2009)
This study extends the analysis of causality by Husain and Rashid (2008) by examining the shift in the variables due to the price hikes in Pakistan in the early 1970s. We investigate the causal relations between real money and real income, between nominal money and nominal income, and between nominal money and prices using the annual data set from 1959-60 to 2003-04. Moreover, we examine the stochastic properties of the variables used in the analysis, and take care of the shifts in the series due to price hikes and liberalisation measures through dummy variables. The results indicate significant shifts in the variables during the sample period. In this context, the shift that occurred due to price hikes in the early 1970s seems to be more important to be incorporated in the analysis. The study finds the active role of money as the leading variable in changing prices without any feedback. In the earlier studies on income the feedback mechanism of money is found missing perhaps because of overlooking the shift in the macro economic variables in the early 1970s. JEL classification: E3, E4, N3 Keywords: Money, Income, Prices, Price Hikes, Causal Relations, Pakistan